PeerJ (PeerJ, 2013)
PeerJ is an Open Access, peer-reviewed, scholarly journal. It considers articles in the Biological Sciences, Medical Sciences, and Health Sciences.
Keywords: lékařství; Biological Phenomena; biologické jevy